2006
DOI: 10.1063/1.2392283
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-optical study of magnetization reversal asymmetry in exchange bias

Abstract: The asymmetric magnetization reversal in exchange biased Fe/MnF 2 involves coherent (Stoner-Wohlfarth) magnetization rotation into an intermediate, stable state perpendicular to the applied field. We provide here experimentally tested analytical conditions for the unambiguous observation of both longitudinal and transverse magnetization components using the magneto-optical Kerr effect. This provides a fast and powerful probe of coherent magnetization reversal as well as its chirality. Surprisingly, the sign an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 19 publications
3
36
0
Order By: Relevance
“…Arenholz et al 8 and Tillmanns et al 9 have observed that in twinned Fe/MnF 2 films, the shape of a kinked hysteresis loop evolves sensitively with the angle between the measurement and bias fields. Other studies have examined the dependence of the magnetization reversal mechanism on the exchange field and anisotropy fields in the samples.…”
mentioning
confidence: 99%
“…Arenholz et al 8 and Tillmanns et al 9 have observed that in twinned Fe/MnF 2 films, the shape of a kinked hysteresis loop evolves sensitively with the angle between the measurement and bias fields. Other studies have examined the dependence of the magnetization reversal mechanism on the exchange field and anisotropy fields in the samples.…”
mentioning
confidence: 99%
“…Coercivity in the front side T-MOKE is not the same as that in the back side, and the amplitudes at the left and right coercivities are asymmetric, indicating that the amount of F spins differ from each other during magnetization rotation between the decreasing and increasing field branches of the T-MOKE loops from the front and back sides of the NiFe/FeMn bilayer. This asymmetric magnetization reversal has been experimentally and theoretically attributed to typical phenomena in a number of exchange-biased F/AF systems [3,[7][8][9][10][11][12][13][14][15][16]. The asymmetric T-MOKE loop for a NiFe/FeMn bilayer seems to originate from the competition between the uniaxial and unidirectional anisotropies [3,13,15].…”
Section: Methodsmentioning
confidence: 99%
“…They claimed that the relative strength of the uniaxial and unidirectional anisotropies is responsible for the different magnetization reversals [15]. The origin of the experimentally observed asymmetry has been addressed as a higher magnetic anisotropy [7], an irreversible change of the AF domain state [8], a partial domain wall parallel to the interface in an F or AF layer [9], an anisotropy dispersion in an F or AF layer [11], the competition between anisotropies [3,13,15], the angle between an applied field direction and a cooling field direction [3,14,17]. Although extensive research has been conducted experimentally and theoretically, the fundamental theory explaining all the features of the magnetization reversal in many F/AF systems remains unknown and controversial due to the inherently complex F/AF spin structure and the difficulty in directly probing the spin configuration and crystallographic structure at an F/AF interface [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] The magnetization reversal mechanisms in EB systems have been the focus of many studies. [4][5][6][7][8][9][10][11][12][13][14] In certain systems asymmetric reversal processes have been observed, where domain nucleation and growth dominate in one field sweep of the hysteresis loop while magnetization rotation prevails in the opposite field sweep. [6][7][8][9] Other studies have shown the dependence of the reversal mechanism on the exchange and anisotropy fields in the sample.…”
mentioning
confidence: 99%